Interlaboratory validation of an optimized protocol for measuring α-amylase activity by the INFOGEST international research network - Daniela Freitas; Shannon Gwala; Gwénaële Henry; Athina Lazaridou; Christine Boesch; Dorine Duijsens; Faye Wheller; Ivan M. Lopez-Rodulfo; Kali Kotsiou; Kendall R. Corbin; Marilisa Alongi; Mario M. Martinez; et al. (Scientific Reports)
Abstract The activity of α-amylases is frequently determined using a single-point assay at 20 °C. Previous work within INFOGEST “Working Group 5 - Starch digestion and amylases” identified significant interlaboratory variation with this protocol. The current study aimed to evaluate the repeatability (intralaboratory precision) and reproducibility (interlaboratory precision), measured as coefficients of variation (CVs), of a newly optimized protocol version based on four time-point measurements at 37 °C. Human saliva (a pool from ten healthy adults) and three porcine enzyme preparations (two pancreatic α-amylases and pancreatin) were tested in 13 laboratories across 12 countries and 3 continents. Assay repeatability for each lab remained below 20% for all test products and the overall repeatability was below 15%, ranging between 8 and 13% for all products. Reproducibility was greatly improved with interlaboratory CVs ranging from 16 to 21%, i.e. up to four times lower than with the original method. Five laboratories repeated the same assay at 20 °C, and the amylolytic activity of each product increased by 3.3-fold (± 0.3) from 20 to 37 °C. The newly optimized protocol is henceforth recommended to ensure precise determinations of α-amylase activity levels and to facilitate comparisons across different studies.